WAHDATUL WUJUD DALAM NASKAH KERATON JAWA: STUDI KOMPARATIF PADA SERAT MENAK DAN SERAT WEDHATAMA - Mahamid, Mochammad Nginwanun Likullil; Hidayatulloh, Hanip (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This study explores the concept of Wahdatul Wujud (Unity of Existence) as depicted in Javanese palace manuscripts, specifically the Serat Menak from Yogyakarta and Serat Wedhatama from Surakarta. Wahdatul Wujud, an Islamic Sufi doctrine, asserts the absolute existence of Allah and has been influential in the spiritual traditions of the Javanese courts since the fragmentation of Islamic Mataram in 1755. Utilizing a descriptive analytic and philology approach, this research examines the implied messages within these manuscripts. The comparative analysis reveals that the Serat Menak, written in Old Javanese (Kawi), presents more complex vocabulary and is harder to understand compared to the Serat Wedhatama. Additionally, while Serat Menak illustrates the Unity of Existence through the narratives of ancient prophets and leaders, Serat Wedhatama conveys it through the Javanese concept of Manunggaling Kawula Gusti (the unity of servant and Lord). These findings underscore the nuanced interpretations of Wahdatul Wujud in Javanese literature and their cultural significance.